2014
DOI: 10.1590/s0100-83582014000400001
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of weed species in monocrop coffee or intercropped with banana, under agroecological system

Abstract: -We aimed with this study to compare weed infestation in coffee under two different cropping managements: conventional coffee grown alone, or intercropped with banana plantation in a year-round basis (late spring, late summer, late fall and late winter). The experiment was installed in 2009 under field conditions at the Escola Municipal Rural Benedita Figueiró de Oliveira, in the city of Ivinhema in the state of Mato Grosso do Sul, Brazil. Assessments of weed occurrence were made three years after employment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…It was also verified in the present study that, when evaluating the number of weeds in relation to the accumulated dry matter, it is confirmed that the higher level of shading promoted by banana trees density affects not only weeds germination but also, as already described by Concenço et al (2014), the growth capacity of these.…”
Section: Indiv M -2supporting
confidence: 89%
See 1 more Smart Citation
“…It was also verified in the present study that, when evaluating the number of weeds in relation to the accumulated dry matter, it is confirmed that the higher level of shading promoted by banana trees density affects not only weeds germination but also, as already described by Concenço et al (2014), the growth capacity of these.…”
Section: Indiv M -2supporting
confidence: 89%
“…Comparing perennial crops such as coffee monoculture (Coffea arabica) with coffee versus banana intercropping and their effect on weed control, Concenço et al (2014) have verified that the presence of banana in the cultivation area has significantly interfered in weed control. Ricci et al (2004), in a study developed in the Brazilian municipality of Seropédica, RJ, in intercropped coffee plantations, have also concluded that coffee cultivation with gliricidia and banana has provided a significant reduction in weeds dry biomass.…”
Section: Phyllanthus Tenellus Digitaria Horizontalis Panicum Maximumentioning
confidence: 94%
“…In high-altitude broadleaved forests, coffee flourishes under mild understory conditions (Wrigley, 1988). Coffee was brought to Brazil in 1727, and as early as 1731, there were reports of the first exports of coffee have been found with shade tree intercropping in coffee plantations, such as: increased air humidity (Araújo, Partelli, Oliosi, & Pezzopane, 2016;Partelli et al, 2014); increased soil organic matter (Melloni et al, 2018); lower soil density, penetration resistance, and higher total porosity, microporosity, and soil water content (Souza et al, 2017); decreased nutrient leaching, improved soil fertility, and reduced fertilizer requirements (Babbar & Zak, 1995;Cuenca, Aranguren, & Herrera, 1983;Fassbender, 1987;Jaramillo-Botero et al, 2010); reduced incidence of Cercospora coffeicola (Berkeley & Cooke;Salgado, Macedo, Carvalho, Salgado, & Venturin, 2007), Leucoptera coffeella (Guérin-Mèneville & Perrottet; Teodoro, Klein, Reis, & Tscharntke, 2009), several species of fruit flies (Diptera: Tephritoidea; Aguiar-Menezes et al, 2007), and weeds (Concenço et al, 2014;Silva, Perdoná, Soratto, & Negrisoli, 2013); as well as improvement in the quality of the harvested coffee beans (Vaast, Bertrand, Perriot, Guyot, & Génard, 2006). On the other hand, the following disadvantages can be noted: lower soil moisture in the dry season (Coelho, Matsumoto, Lemos, & Souza, 2010;Neves, Martinez, Souza, & Cecon, 2007), higher incidence of Hypothenemus hampei (Ferrari; Wrigley, 1988), need for pruning to regulate shading provided by trees to coffee plants, and, mainly, limitation of coffee production potential and mechanized cultural practices, especially mechanized coffee harvesting (Perdoná & Soratto, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In many areas of Mexico and the world, intensive coffee monoculture is practiced in mountainous areas (Perfecto et al, 2019), where the soil is fully exposed to natural erosion factors (DaMatta and Rena 2002). In addition, the large amounts of agrochemicals used in intensive systems contribute to the contamination of surface water and aquifers, decrease soil biodiversity, favor the appearance of secondary pests, and increase pesticide resistance in pests (Muschler 2004), since weed infestation is common (Concenco et al 2014). The increased use of agrochemicals could accelerate soil degradation (Castro-Tanzi et al 2014), especially in incipient or highly weathered soils, which are more fragile.…”
Section: Introductionmentioning
confidence: 99%